2020
DOI: 10.1128/jvi.01798-19
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Murine CD80 by Herpes Simplex Virus 1 in Place of Latency-Associated Transcript (LAT) Can Compensate for Latency Reactivation and Anti-apoptotic Functions of LAT

Abstract: High rates of wild-type (WT) herpes simplex virus 1 (HSV-1) latency reactivation depend on the anti-apoptotic activities of latency-associated transcript (LAT). Replacing LAT with the baculovirus inhibitor of apoptosis protein (cpIAP) or cellular FLIP (FLICE-like inhibitory protein) gene restored the WT latency reactivation phenotype to that of a LAT-minus [LAT(−)] virus, while similar recombinant viruses expressing interleukin-4 (IL-4) or interferon gamma (IFN-γ) did not. However, HSV-1 recombinant virus expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 73 publications
0
20
0
Order By: Relevance
“…Mice were sacrificed on day 28 PI and individual TG were removed and cultured in tissue culture media as described [ 19 , 20 , 59 ]. Aliquots of media were removed from each culture daily and plated on indicator cells (RS cells) to detect reactivated virus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice were sacrificed on day 28 PI and individual TG were removed and cultured in tissue culture media as described [ 19 , 20 , 59 ]. Aliquots of media were removed from each culture daily and plated on indicator cells (RS cells) to detect reactivated virus.…”
Section: Methodsmentioning
confidence: 99%
“…TG from individual mice were collected on day 28 PI, immersed in RNA later, RNA Stabilization Reagent (Thermo Fisher Scientific, Waltham, MA, USA), and stored at −80°C until processing. Total RNA was extracted as described [ 19 , 20 , 59 ]. Levels of LAT RNA from latent TG were determined using a custom-made LAT primers and probe as follows: forward primer, 5′-GGGTGGGCTCGTGTTACAG-3′; reverse primer, 5′-GGACGGGTAAGTAACAGAGTCT CTA-3′; and probe, 5′-FAM-ACACCAGCCCGTTCTTT-3′ (amplicon length = 81 bp).…”
Section: Methodsmentioning
confidence: 99%
“…Despite the potentiation of apoptosis reported above, it is established that inhibition of apoptosis is critical for the reactivation of latency by HSV [ 80 ], and this mechanism is mediated by the action of the latency-associated transcript (LAT), which is the only HSV transcript expressed significantly during latency. Another recent study showed that CD80 can compensate for the functions of the LAT, such as the establishment of latency, reactivation and immune exhaustion in cells infected with the LAT-null virus [ 81 ]. This is significant because this is the first time that such overlapping functionalities between LAT and CD80 have been reported.…”
Section: Hsv Immune Evasion Mechanismsmentioning
confidence: 99%
“…Although CD80 rescues the functions of LAT, it has distinct functions as CD80 exacerbated eye disease in mice compared to wild-type HSV. Furthermore, CD80 potentiated the expression of the anti-apoptotic Bcl-2 gene thus modulating apoptosis in the infected cells [ 81 ]. Another HSV-1 protein that has implications in regulating cellular apoptosis—ICP22 has been shown to function via a mechanism like that used by the cellular J-protein/HSP40 family chaperone [ 82 ].…”
Section: Hsv Immune Evasion Mechanismsmentioning
confidence: 99%
“…HSV-1 evades clearance by the host immune system through a variety of mechanisms to establish lifelong latent infection ( Kurt-Jones et al, 2017 ; Lin and Zheng, 2019 ; Tognarelli et al, 2019 ; Zhu and Zheng, 2020 ). For example, HSV-1 LAT plays a vital role in generating dysfunctional T-cell responses in the TG of ocular infected HSV-1 mice and helps the virus resist host cell apoptosis by inhibiting the type I IFN signaling pathway, thus contributing to the establishment and activation of latent HSV-1 infection ( Perng et al, 2000 ; Branco and Fraser, 2005 ; Allen et al, 2011 ; Tormanen et al, 2019 ; Jaggi et al, 2020 ). LAT-containing neurons are occasionally surrounded by CD8 + T cells ( Theil et al, 2003 ; Verjans et al, 2007 ) that are primed in the periphery ( Held et al, 2011 ) and LAT functions in part to protect neurons against granzyme B–induced apoptosis ( Allen et al, 2011 ; Jiang et al, 2011 ).…”
Section: Roles Of Icp22/orf63 In Viral Latency and Reactivationmentioning
confidence: 99%